Composite three-dimensional copper current collector, preparation method thereof and lithium metal battery
By combining self-assembled molecules on the surface of the three-dimensional copper current collector, its oxidation resistance and corrosion resistance are improved, and the problems of easy oxidation of three-dimensional copper current collectors and lithium dendrites are solved, which significantly improves the electrochemical performance of lithium metal batteries.
Patent Information
- Application Number
- CN202411663628.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-21
AI Technical Summary
The existing three-dimensional copper current collectors have weak oxidation resistance due to their high specific surface area, are prone to oxidation and are not resistant to corrosion, resulting in the formation of lithium dendrites and the reduction of battery performance.
By combining self-assembled molecules on the surface of the three-dimensional copper current collector, the surface is modified, and the contact area between the current collector and the electrolyte is reduced, thereby inhibiting side reactions and the formation of lithium dendrites.
It significantly improves the ratio and cycle stability of lithium metal batteries, and reduces the formation of lithium dendrites and the safety risks of batteries.
Smart Images

Figure CN119495750A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a composite three-dimensional copper current collector and a preparation method thereof, and a lithium metal battery. Background Art
[0002] As the demand for portable electronic products and electric vehicles becomes increasingly urgent, rechargeable batteries, as a dominant lightweight power source, are essential to the development of human society. In terms of energy density, lithium metal is an ideal anode material with excellent specific capacity (up to 3860 mAh g -1 ) and has a lower reduction potential (-3.04V compared to the standard hydrogen electrode). However, current lithium-ion batteries still need further improvement if they are to meet the ever-increasing energy density requirements and the rapid development of large-scale energy storage technology, and they still face huge challenges. The use of lithium metal as an anode usually faces some obstacles, the most challenging of which is the formation of lithium dendrites during the cycle, which leads to low Coulombic efficiency, short cycle life, internal short circuit and even catastrophic battery failure. Lithium metal batteries also face a wide range of safety issues.
[0003] In recent years, research on lithium-free anodes and thin lithium anode lithium metal batteries has received widespread attention. At present, a lot of efforts have been made to prevent dendrite growth and improve the stability of lithium metal anodes, including interface regulation strategies, anode structure engineering, electrolyte optimization, stress release strategies and the use of self-healing mechanisms. It is generally believed that dendrite growth is caused by uneven current and ion distribution on the anode surface, and the current collector has an important influence on the performance of the electrode. By designing the current collector, the current density and ion diffusion on the anode surface can be optimized. The current density and ion concentration on the surface of the commonly used planar copper current collector are very easy to be unevenly distributed. During the electrodeposition process, lithium metal is easy to grow in the direction of the dendrite, causing short circuits and serious safety hazards; in addition, uneven plating / stripping of lithium metal can also lead to dendrite growth, resulting in low Coulomb efficiency.
[0004] Compared with planar (two-dimensional) copper current collectors, the structure of three-dimensional copper current collectors is conducive to the uniform distribution of surface current density and ion flux, and provides sufficient internal space for the deposited lithium metal, which can effectively alleviate the formation of lithium metal dendrites to a certain extent.
[0005] However, the three-dimensional copper current collector has a high specific surface area, which results in weak antioxidant capacity. It is very easy to oxidize and is not corrosion-resistant during the preparation process, which inevitably forms lithium dendrites. In addition, its porous structure increases the contact area between the electrolyte and the current collector, thereby increasing the occurrence of side reactions and causing problems such as increased interface resistance. Studies have shown that the design of molecular self-assembled layers on the electrode surface plays an important role as interface nanomaterials in rechargeable battery applications, which can promote the formation of SEI, inhibit the generation of dendrites, inhibit electrode side reactions, and promote reversible Li insertion.
[0006] Therefore, how to improve the above-mentioned problems faced by three-dimensional copper current collectors as electrodes of lithium metal batteries, and then improve the rate and cycle stability of lithium metal batteries, has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a composite three-dimensional copper current collector and a preparation method thereof and a lithium metal battery. The present invention combines self-assembly molecules on the surface of the three-dimensional copper current collector to modify it, and combines the three-dimensional copper current collector with different functions, which is thin, light and has good mechanical properties, but has poor corrosion resistance, weak antioxidant ability and many surface side reactions after assembling the battery, with self-assembly molecules, so as to improve the three-dimensional copper current collector, such as easy oxidation and corrosion resistance, surface side reactions and lithium dendrite growth. The three-dimensional copper current collector can be modified in different aspects, and the composite three-dimensional copper current collector can be applied in lithium metal batteries, which can significantly improve the electrochemical properties of lithium metal batteries, such as rate and cycle stability.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a composite three-dimensional copper current collector, the composite three-dimensional copper current collector comprising a three-dimensional copper current collector and self-assembly molecules;
[0010] The three-dimensional copper current collector includes a copper foil and a copper-nickel alloy nanocone supported on one side surface of the copper foil;
[0011] The self-assembly molecules are combined on the surface of the copper-nickel alloy nanocones.
[0012] The present invention combines a three-dimensional copper current collector with self-assembling molecules. The surface of the three-dimensional copper current collector is partially (completely) coated by the self-assembling molecules, which can greatly alleviate the phenomenon that the surface of the three-dimensional copper current collector is corroded due to its large specific surface area, and can also reduce the contact area between the current collector and the electrolyte, reduce side reactions, and alleviate the formation of lithium dendrites during battery operation. In addition, different self-assembling molecules can be used to modify the three-dimensional copper current collector in different aspects. The composite three-dimensional copper current collector of the present invention is applied to a lithium metal battery, which can significantly improve the electrochemical properties of the lithium metal battery, such as the rate and cycle stability.
[0013] The present invention adopts a copper current collector with a three-dimensional structure. On the one hand, during the lithium deposition process, the copper-nickel alloy nanocone structure on the surface of the copper-nickel alloy has a protruding tip on the submicron cone structure as a charge center and a nucleation site, the electric field is roughly uniform, and the charge is evenly dispersed along the cone structure. Lithium metal nucleates and grows on the copper-nickel alloy nanocone to form nano-sized agglomerates, which fill the pores of the three-dimensional copper current collector and further form a relatively uniform lithium surface. On the other hand, the lithium nucleation overpotential and local current density are reduced, and the adsorption, nucleation and deposition process of lithium ions on the "three-dimensional copper current collector-electrolyte" interface are significantly improved, and the reversibility and kinetics of the lithium metal deposition-stripping process are improved. Compared with the planar copper current collector with a two-dimensional structure, the copper current collector with a three-dimensional structure has certain ductility and mechanical properties, and exhibits effective stress dissipation to adapt to the volume change during the lithium plating process. Even under high-rate conditions, it helps to reduce the local effective current density, uniform electric field distribution and reduce the lithium ion concentration gradient, so that the lithium metal is uniformly nucleated and deposited densely during the lithium deposition process, and the formation of lithium dendrites is significantly reduced.
[0014] As a preferred technical solution of the present invention, the copper-nickel alloy nanocones are arranged in an array.
[0015] In the present invention, the copper-nickel alloy nanocones are arranged in a random array.
[0016] Preferably, the height of the copper-nickel alloy nanocones is 3.5-20 μm, for example, 3.5 μm, 5 μm, 7.5 μm, 10 μm, 12.5 μm, 15 μm, 17.5 μm or 20 μm.
[0017] Preferably, the bottom diameter of the copper-nickel alloy nanocone is 800-1500 nm, for example, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm or 1500 nm.
[0018] Preferably, the density of the copper-nickel alloy nanocones is 1×10 6 ~1×10 7 Pieces / mm 2 , for example 1×10 6 Pieces / mm 2 , 1.2×10 6 Pieces / mm 2 , 1.4×10 6 Pieces / mm 2 , 1.6×10 6 Pieces / mm 2 , 1.8×10 6 Pieces / mm 2 or 1×10 7 Pieces / mm2 wait.
[0019] As a preferred technical solution of the present invention, the self-assembling molecules include long-chain self-assembling molecules and / or short-chain self-assembling molecules.
[0020] It should be noted that the self-assembling molecules in the present invention can be divided into two categories: aliphatic hydrocarbons and aromatic hydrocarbons. The aliphatic hydrocarbons with a carbon number of less than 10 in the main chain are short-chain self-assembling molecules, and the aliphatic hydrocarbons with a carbon number ≥10 are long-chain self-assembling molecules. In the longest substituent of the aromatic hydrocarbon, the aliphatic hydrocarbons with a carbon number of less than 10 are short-chain self-assembling molecules, and the aliphatic hydrocarbons with a carbon number ≥10 are long-chain self-assembling molecules. In the present invention, a single long-chain self-assembling molecule can be combined with the surface of a three-dimensional copper current collector, a single short-chain self-assembling molecule can be combined with the surface of a three-dimensional copper current collector, or a long-chain self-assembling molecule and a short-chain self-assembling molecule can be combined with the surface of a three-dimensional copper current collector.
[0021] In the present invention, when a single long-chain self-assembling molecule is combined with the surface of a three-dimensional copper current collector, in addition to improving the phenomenon that the three-dimensional copper current collector is easy to oxidize and not resistant to corrosion, surface side reactions and lithium dendrite growth, it also has a greater steric hindrance, making it easier to remove organic solvents and release lithium ions, which has a beneficial effect on solvation removal; when a single short-chain self-assembling molecule is combined with the surface of a three-dimensional copper current collector, the short-chain self-assembling molecule has a smaller steric hindrance, which can better achieve the coating effect, and thus better play a corresponding role, such as a hydrophobic effect, which can largely avoid the corrosion of the three-dimensional copper current collector surface; When the long-chain self-assembly molecules and the short-chain self-assembly molecules are combined with the surface of the three-dimensional copper current collector, the two play a synergistic role. Since the long-chain self-assembly molecules have a large steric hindrance, after they self-assemble with the three-dimensional copper current collector, there are still sites on the surface of the three-dimensional copper current collector that are not completely covered. Further assembly of the short-chain self-assembly molecules with smaller steric hindrance can cover the uncoated sites. The two work together to make the coating denser, making the performance of the modified composite three-dimensional copper current collector better, thereby better improving the electrochemical properties of lithium metal batteries such as the rate and cycle stability.
[0022] Preferably, the long-chain self-assembling molecules and the short-chain self-assembling molecules each independently include a group of an element containing a lone pair of electrons.
[0023] Preferably, the element containing a lone pair of electrons includes any one of S, O or N, or a combination of at least two of them.
[0024] The long-chain self-assembly molecules and the short-chain self-assembly molecules of the present invention independently include groups of elements containing lone pair electrons, wherein the lone pair electrons can be adsorbed by hybridization with the 3d orbit of Cu, and then combined to be coated on the surface of the three-dimensional copper current collector.
[0025] It should be noted that, in the long-chain self-assembly molecules and the short-chain self-assembly molecules, except for the groups containing elements with lone pairs of electrons, the remaining groups are not limited and can be adjusted and selected according to actual needs. For example, they can be alkyl carbon chains that have a hydrophobic effect, fluorine-containing groups that have an electrolyte-repelling effect and promote the formation of favorable components in SEI, aromatic groups that promote electron conduction, or azo groups that promote lithium affinity, etc.
[0026] Preferably, the long-chain self-assembling molecules include any one or a combination of at least two of dihexadecyl phosphate, n-octadecyl phosphate, perfluorotetradecyl phosphate, n-tetradecyl mercaptan, n-hexadecyl mercaptan or n-octadecyl mercaptan.
[0027] Preferably, the short-chain self-assembly molecule comprises any one of thiocyanuric acid, melamine, cyanuric acid, benzotriazole, 2-mercaptobenzothiazole, thiourea, urea, n-butyl mercaptan, n-pentyl mercaptan, n-hexyl mercaptan, n-heptyl mercaptan or n-octyl mercaptan, or a combination of at least two thereof.
[0028] It should be noted that the present invention does not make any specific requirements or special limitations on the type and form of the copper foil. As long as the type and form are commonly used by technical personnel in the field, they are applicable to the present invention. For example, it can be commercial copper foil, composite copper foil or copper alloy, and the form can be flat copper foil or curved copper foil, etc.
[0029] In a second aspect, the present invention further provides a method for preparing the composite three-dimensional copper current collector according to the first aspect, the preparation method comprising the following steps:
[0030] A constant current electrodeposition process is adopted to load copper-nickel alloy nanocones on the surface of copper foil to obtain a three-dimensional copper current collector; and self-assembly molecules are then combined on the surface of the three-dimensional copper current collector to obtain a composite three-dimensional copper current collector.
[0031] As a preferred technical solution of the present invention, the current density of the constant current electrodeposition is 2-2.5 mA / cm 2 , for example 2mA / cm 2 , 2.1mA / cm 2 , 2.2mA / cm 2 , 2.3mA / cm 2 , 2.4mA / cm 2 or 2.5mA / cm 2 wait.
[0032] Preferably, the deposition time of the constant current electrodeposition is 10-100 min, for example, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or 100 min, etc.
[0033] The current density of the constant current electrodeposition of the present invention is 2-2.5 mA / cm 2 , the deposition time is 10-100min, and a copper-nickel alloy nanocone structure with a better morphology can be prepared. After the composite three-dimensional copper current collector obtained by combining with the self-assembly molecules is assembled into a battery, it is expected to achieve uniform nucleation of lithium metal, dendrite-free deposition and reduce surface side reactions. At the same time, it can inhibit the volume expansion of the electrode and has better rate and cycle stability. If the current density is too large, the copper-nickel alloy nanocone structure on the surface of the copper foil will be sparse, and the uniformity and density of the lithium deposition process will be reduced, which will lead to the formation of lithium dendrites; if the current density is too low, only a particle film layer can be formed on the surface of the copper foil, and the copper-nickel alloy nanocone structure cannot be obtained; if the deposition time is too long, a uniform nickel alloy nanocone structure cannot be obtained, and the obtained structure is a rod-like structure; if the deposition time is too short, the copper-nickel alloy nanocone structure still cannot be obtained, and only a nanosheet structure can be formed on the surface of the copper foil.
[0034] Preferably, the working electrode of the constant current electrodeposition is the copper foil, and the counter electrode is a copper sheet with the same area as the copper foil in the working electrode.
[0035] Preferably, the distance between the working electrode and the counter electrode is 1-5 cm, for example, 1 cm, 2 cm, 3 cm, 4 cm or 5 cm.
[0036] As a preferred technical solution of the present invention, the copper foil also includes removing the oxide layer and drying with high-purity nitrogen before the electrodeposition process.
[0037] Preferably, the electrolyte of the electrodeposition process comprises copper sulfate, sodium hypophosphite, nickel sulfate, trisodium citrate, boric acid, polyethylene glycol and sodium hydroxide.
[0038] Preferably, in the electrolyte, the concentration of copper sulfate is 0.02-0.04 mol / L, such as 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.035 mol / L or 0.04 mol / L, etc.; the concentration of sodium hypophosphite is 0.1-0.4 mol / L, such as 0.1 mol / L, 0.2 mol / L, 0.3 mol / L or 0.4 mol / L, etc.; the concentration of nickel sulfate is 0.0015-0.005 mol / L, such as 0.0015 mol / L, 0.0025 mol / L, 0.0035 mol / L , 0.0045mol / L or 0.005mol / L, etc.; the concentration of trisodium citrate is 0.03-0.07mol / L, for example, 0.03mol / L, 0.04mol / L, 0.05mol / L, 0.06mol / L or 0.07mol / L, etc.; the concentration of boric acid is 0.3-1mol / L, for example, 0.3mol / L, 0.5mol / L, 0.7mol / L or 1mol / L, etc.; the concentration of polyethylene glycol is 1-15g / L, for example, 1g / L, 3g / L, 5g / L, 7g / L, 9g / L, 12g / L or 15g / L, etc.
[0039] Preferably, the temperature of the electrolyte is 60-80°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, etc.
[0040] Preferably, the pH of the electrolyte is 7-9, for example, 7, 7.2, 7.5, 7.8, 8, 8.2, 8.5, 8.8 or 9.
[0041] As a preferred technical solution of the present invention, the method used for combining the self-assembling molecules includes a liquid phase method or a vapor phase deposition method, preferably a liquid phase method.
[0042] Preferably, the liquid phase coating method comprises the following steps:
[0043] The three-dimensional copper current collector is immersed in a solution containing self-assembly molecules and placed in a constant temperature water bath, so that the self-assembly molecules are combined with the surface of the three-dimensional copper current collector.
[0044] As a preferred technical solution of the present invention, the solvent containing the self-assembling molecule solution includes any one of anhydrous ethanol, tetrahydrofuran, anhydrous cyclohexane, toluene or dimethyl sulfoxide, or a combination of at least two thereof.
[0045] Preferably, the temperature of the constant temperature water bath is 50-120°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C.
[0046] Preferably, the constant temperature water bath time is 1-120 min, for example, 1 min, 20 min, 40 min, 60 min, 80 min, 100 min or 120 min, etc.
[0047] Preferably, after the constant temperature water bath, the surface is rinsed.
[0048] Preferably, said rinsing the surface comprises rinsing the surface with said solvent.
[0049] Preferably, before obtaining the composite three-dimensional copper current collector, surface drying and vacuum drying are also included.
[0050] Preferably, the surface drying comprises blowing the surface dry with high-purity nitrogen.
[0051] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0052] The copper foil is used as a working electrode after removing the oxide layer and being blown dry with high-purity nitrogen. A copper sheet with the same area as the copper foil in the working electrode is used as a counter electrode. The distance between the working electrode and the counter electrode is 1-5 cm. The electrolyte includes 0.02-0.04 mol / L copper sulfate, 0.1-0.4 mol / L sodium hypophosphite, 0.0015-0.005 mol / L nickel sulfate, 0.03-0.07 mol / L trisodium citrate, 0.3-1 mol / L boric acid, 1-15 g / L polyethylene glycol and sodium hydroxide. The pH of the electrolyte is 7-9, the temperature is 60-80° C., and constant current electrodeposition is used at 2-2.5 mA / cm 2 The copper foil electrode is deposited for 10-100 minutes to obtain a three-dimensional copper current collector;
[0053] After removing the oxide layer of the three-dimensional copper current collector and drying it with high-purity nitrogen, immerse it in a solution containing self-assembled molecules, immerse it in a constant temperature water bath of 50-120° C. for 1-120 minutes, so that the self-assembled molecules are combined with the surface of the three-dimensional copper current collector. After the immersion is completed, rinse the surface, dry it with high-purity nitrogen, and vacuum dry it to obtain a composite three-dimensional copper current collector;
[0054] Wherein, the self-assembling molecules include long-chain self-assembling molecules and / or short-chain self-assembling molecules.
[0055] In a third aspect, the present invention further provides a lithium metal battery, comprising the composite three-dimensional copper current collector as described in the first aspect, or the composite three-dimensional copper current collector prepared by the preparation method described in the second aspect.
[0056] Preferably, the lithium metal battery comprises a liquid lithium metal battery or a solid lithium metal battery.
[0057] Compared with the prior art, the present invention has at least the following beneficial effects:
[0058] 1) The present invention combines self-assembling molecules on the surface of a three-dimensional copper current collector, and the surface of the three-dimensional copper current collector is partially (completely) coated with the self-assembling molecules, which can greatly alleviate the phenomenon that the surface of the three-dimensional copper current collector has weak antioxidant ability due to its large specific surface area, and can also reduce the contact area between the current collector and the electrolyte, reduce surface side reactions, and alleviate the formation of lithium dendrites.
[0059] 2) The present invention can also modify the three-dimensional copper current collector in different aspects by using different self-assembly molecules. The application of the composite three-dimensional copper current collector in lithium metal batteries can significantly improve the electrochemical properties of lithium metal batteries, such as rate and cycle stability.
[0060] 3) The present invention utilizes a three-dimensional copper current collector, which can effectively reduce the quality of the current collector and the cost of the battery, and is expected to better match the production needs of the modern battery industry.
[0061] 4) The present invention has a simple preparation process, low preparation cost, controllable morphology and size, and multiple raw material selectivities, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a local scanning electron microscope image of the three-dimensional copper current collector of Example 1 of the present invention.
[0063] Figure 2 This is a SEM oblique view of the three-dimensional copper current collector of Example 1 of the present invention after being squeezed under a pressure of 500 kg.
[0064] Figure 3 It is a schematic diagram of the structure of the composite three-dimensional copper current collector of Example 1 of the present invention.
[0065] Figure 4 This is an Auger electron spectrum diagram of the composite three-dimensional copper current collector of Example 3 of the present invention.
[0066] Figure 5 This is a surface SEM image of the composite three-dimensional copper current collector after lithium plating in Example 3 of the present invention.
[0067] Figure 6 This is a cross-sectional SEM image of the composite three-dimensional copper current collector after lithium plating in Example 3 of the present invention.
[0068] Figure 7 This is a surface SEM image of the composite three-dimensional copper current collector of Example 5 of the present invention.
[0069] Figure 8 This is a cross-sectional SEM image of the composite three-dimensional copper current collector of Example 5 of the present invention.
[0070] Fig. 9 This is a surface SEM image of the composite three-dimensional copper current collector of Example 6 of the present invention.
[0071] Fig.10 This is a cross-sectional SEM image of the composite three-dimensional copper current collector of Example 6 of the present invention.
[0072] Fig.11 This is a surface SEM image of the composite three-dimensional copper current collector of Example 7 of the present invention.
[0073] Fig.12 This is a cross-sectional SEM image of the composite three-dimensional copper current collector of Example 7 of the present invention.
[0074] Fig.13 This is a surface SEM image of the composite three-dimensional copper current collector of Example 8 of the present invention.
[0075] Fig.14 This is a cross-sectional SEM image of the composite three-dimensional copper current collector of Example 8 of the present invention.
[0076] Fig.15 It is a comparison chart of the symmetrical battery cycle performance between Application Example 11 of the present invention and Comparative Application Example 4. DETAILED DESCRIPTION
[0077] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0078] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0079] Example 1
[0080] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof, wherein the composite three-dimensional copper current collector comprises a three-dimensional copper current collector and dihexadecyl phosphate and n-hexyl mercaptan bound to the surface of the three-dimensional copper current collector; the three-dimensional copper current collector comprises a copper foil and a copper-nickel alloy nanocone loaded on the surface of the copper foil;
[0081] The preparation method comprises the following steps:
[0082] A flat commercial copper foil was rinsed with dilute hydrochloric acid, deionized water, acetone and deionized water in sequence, and the surface was dried with high-purity nitrogen. An electrolyte was prepared with the following composition: 0.03 mol / L copper sulfate, 0.24 mol / L sodium hypophosphite, 0.0024 mol / L nickel sulfate, 0.05 mol / L trisodium citrate, 0.5 mol / L boric acid, and 6 g / L polyethylene glycol. Sodium hydroxide was prepared to obtain a 4 mol / L sodium hydroxide solution, and the pH of the electrolyte was adjusted to 8.0 with the sodium hydroxide solution. The treated flat commercial copper foil was used as a working electrode, and a copper sheet of the same area was polished as a counter electrode. The distance between the two electrodes was 3 cm, the electrolyte temperature was controlled at 70°C, a magnetic stirring was added, and constant current electrodeposition was used at 2.2 mA / cm 2 The copper foil electrode was deposited for 20 min at a current density of , and a three-dimensional copper current collector was obtained;
[0083] The three-dimensional copper current collector is dried by high-purity nitrogen after removing the oxide layer, and a 0.1wt% dihexadecyl phosphate (DHP) solution is prepared by using tetrahydrofuran as a solvent, and the solution temperature is controlled at 60° C. in a constant temperature water bath, and the treated three-dimensional copper current collector is immersed in the solution for 30 minutes, and then the surface is rinsed with tetrahydrofuran to obtain a three-dimensional copper current collector with dihexadecyl phosphate bound to the surface;
[0084] Tetrahydrofuran is used as a solvent to prepare a 1wt% n-hexyl mercaptan solution, the solution temperature is controlled at 60°C in a constant temperature water bath, and the three-dimensional copper current collector with dihexadecyl phosphate bound to the surface is immersed therein for 60 minutes, and then the surface is rinsed with tetrahydrofuran, and the surface is blown dry with high-purity nitrogen gas, and vacuum dried to obtain a composite three-dimensional copper current collector.
[0085] Figure 1 The local scanning electron microscope image of the three-dimensional copper current collector of Example 1 is shown. It can be seen from the figure that the copper-nickel alloy nanocones are arranged in a random array. Statistics show that the density of the copper-nickel alloy nanocones on the surface of the three-dimensional copper current collector is about 1.2×10 6 Pieces / mm 2 , the height is 3.98±0.32μm, and the bottom diameter is about 865±93nm.
[0086] Figure 2 The SEM oblique view of the three-dimensional copper current collector of Example 1 after being squeezed under a pressure of 500 kg is shown. It can be seen from the figure that the nanocones of the composite three-dimensional copper current collector can withstand a pressure of 5.6 MPa (corresponding to 500 kg) without deformation.
[0087] Figure 3 The schematic structural diagram of the composite three-dimensional copper current collector of Example 1 is shown. As can be seen from the figure, the long-chain dihexadecyl phosphate and the short-chain n-hexyl mercaptan are simultaneously combined with the three-dimensional copper current collector to form a dense coating.
[0088] Example 2
[0089] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof, wherein the composite three-dimensional copper current collector comprises a three-dimensional copper current collector and n-octadecyl mercaptan and melamine bound to the surface of the three-dimensional copper current collector; the three-dimensional copper current collector comprises a copper foil and a copper-nickel alloy nanocone supported on the surface of the copper foil;
[0090] The preparation method comprises the following steps:
[0091] A flat commercial copper foil was rinsed with dilute hydrochloric acid, deionized water, acetone and deionized water in sequence, and the surface was dried with high-purity nitrogen. An electrolyte was prepared, and the composition was: 0.02 mol / L copper sulfate, 0.4 mol / L sodium hypophosphite, 0.0015 mol / L nickel sulfate, 0.07 mol / L trisodium citrate, 0.3 mol / L boric acid, 15 g / L polyethylene glycol. Sodium hydroxide was prepared to obtain a 4 mol / L sodium hydroxide solution, and the pH of the electrolyte was adjusted to 9.0 with the sodium hydroxide solution. The treated flat commercial copper foil was used as a working electrode, and a copper sheet of the same area was polished as a counter electrode. The distance between the two electrodes was 3 cm, the electrolyte temperature was controlled at 60 ° C, a magnetic stirring was added, and constant current electrodeposition was used at 2.5 mA / cm 2 The copper foil electrode was deposited for 20 min at a current density of , and a three-dimensional copper current collector was obtained;
[0092] The three-dimensional copper current collector is dried by removing the oxide layer and blowing with high-purity nitrogen, and anhydrous ethanol is used as a solvent to prepare a 1wt% n-octadecyl mercaptan solution, and the solution temperature is controlled at 50° C. in a constant temperature water bath, and the treated three-dimensional copper current collector is immersed in the solution for 60 minutes, and then the surface is rinsed with anhydrous ethanol to obtain a three-dimensional copper current collector with n-octadecyl mercaptan bound to the surface;
[0093] Anhydrous ethanol was used as a solvent to prepare a 2.5 mmol / L melamine solution. The solution temperature was controlled at 50°C in a constant temperature water bath. The three-dimensional copper current collector with n-octadecyl mercaptan bound to the surface was immersed in the solution for 2 minutes. The surface was then rinsed with anhydrous ethanol and dried with high-purity nitrogen. After vacuum drying, a composite three-dimensional copper current collector was obtained.
[0094] Example 3
[0095] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof, wherein the composite three-dimensional copper current collector comprises a three-dimensional copper current collector and thiocyanate bound to the surface of the three-dimensional copper current collector; the three-dimensional copper current collector comprises a copper foil and a copper-nickel alloy nanocone loaded on the surface of the copper foil;
[0096] The preparation method comprises the following steps:
[0097] A flat commercial copper foil was rinsed with dilute hydrochloric acid, deionized water, acetone and deionized water in sequence, and the surface was dried with high-purity nitrogen. An electrolyte was prepared, and the composition was: 0.04 mol / L copper sulfate, 0.1 mol / L sodium hypophosphite, 0.005 mol / L nickel sulfate, 0.03 mol / L trisodium citrate, 0.1 mol / L boric acid, 1 g / L polyethylene glycol. Sodium hydroxide was prepared to obtain a 4 mol / L sodium hydroxide solution, and the pH of the electrolyte was adjusted to 7.0 with the sodium hydroxide solution. The treated flat commercial copper foil was used as a working electrode, and a copper sheet of the same area was polished as a counter electrode. The distance between the two electrodes was 1 cm, the electrolyte temperature was controlled at 80°C, a magnetic stirring was added, and constant current electrodeposition was used at 2 mA / cm 2 The copper foil electrode was deposited for 100 min at a current density of 1.5 to obtain a three-dimensional copper current collector.
[0098] The oxide layer of the three-dimensional copper current collector is removed and dried with high-purity nitrogen. Anhydrous ethanol is used as a solvent to prepare a 2.5 mmol / L trithiocyanic acid (TTCA) solution. The solution temperature is controlled at 50° C. in a constant temperature water bath. The treated three-dimensional copper current collector is immersed in the solution for 3 minutes. The surface is then rinsed with anhydrous ethanol, and the surface is dried with high-purity nitrogen. After vacuum drying, a composite three-dimensional copper current collector is obtained.
[0099] Figure 4 The Auger electron spectrum of the composite three-dimensional copper current collector prepared in Example 3 is shown. It can be seen from the figure that its surface contains rich characteristic elements in the TTCA structure such as C, S and N, which further shows that TTCA can be evenly distributed on the surface of the three-dimensional copper current collector.
[0100] The composite three-dimensional copper current collector prepared in this example was used as the positive electrode, the lithium sheet was used as the negative electrode, and the electrolyte was composed of 1M LiTFSI, DOL / DME (volume ratio 1:1), 2% LiNO 3 Ether-based electrolyte, using 1.5mA / cm 2 The current density of lithium plating on the surface is 5mAh / cm 2 , then disassemble the battery in the glove box, take out the lithium-plated current collector, rinse it with DME solution, and dry it.
[0101] Figure 5 The surface SEM image of the composite three-dimensional copper current collector after lithium plating in Example 3 is shown. Figure 6 The cross-sectional SEM image of the three-dimensional copper current collector after lithium plating in Example 3 is shown. As can be seen from the image, no dendritic lithium morphology appears, the lithium metal is densely stacked, and the lithium plating is uniform.
[0102] Example 4
[0103] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof, wherein the composite three-dimensional copper current collector comprises a three-dimensional copper current collector and dihexadecyl phosphate bound to the surface of the three-dimensional copper current collector; the three-dimensional copper current collector comprises a copper foil and a copper-nickel alloy nanocone loaded on the surface of the copper foil;
[0104] The preparation method comprises the following steps:
[0105] The preparation method of the three-dimensional copper current collector is consistent with that of Example 1;
[0106] The oxide layer of the three-dimensional copper current collector is removed and dried with high-purity nitrogen, and a 0.1wt% dihexadecyl phosphate solution is prepared using tetrahydrofuran as a solvent. The solution temperature is controlled at 60°C in a constant temperature water bath, and the treated three-dimensional copper current collector is immersed in the solution for 30 minutes. The surface is then rinsed with tetrahydrofuran, and the surface is dried with high-purity nitrogen. After vacuum drying, a composite three-dimensional copper current collector is obtained.
[0107] Example 5
[0108] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof. The difference between the preparation method and Example 1 is that the current density of the constant current electrodeposition is 1 mA / cm 2 The rest of the preparation method and parameters are consistent with Example 1.
[0109] Figure 7 The surface SEM image of the composite three-dimensional copper current collector of Example 5 is shown. Figure 8 The cross-sectional SEM image of the composite three-dimensional copper current collector of Example 5 is shown. It can be seen from the figure that when the current density is too low, the nanocone structure cannot be formed on the surface, but a particle film is present, which is not conducive to the uniform deposition of lithium metal.
[0110] Example 6
[0111] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof. The difference between the preparation method and Example 1 is that the current density of the constant current electrodeposition is 3.5 mA / cm 2 The rest of the preparation method and parameters are consistent with Example 1.
[0112] Fig. 9 The surface SEM image of the composite three-dimensional copper current collector of Example 6 is shown. Fig.10 The cross-sectional SEM image of the composite three-dimensional copper current collector of Example 6 is shown. It can be seen from the figure that although copper nanocone morphology can grow on the surface of the flat copper foil, there are ungrown areas on the surface, the nanocone structure has poor uniformity and low density, and this morphology will affect the uniform deposition of lithium metal.
[0113] Example 7
[0114] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof. The preparation method is different from that in Example 1 in that the deposition time of constant current electrodeposition is 135 min, and the other preparation methods and parameters are consistent with those in Example 1.
[0115] Fig.11 The surface SEM image of the composite three-dimensional copper current collector of Example 7 is shown. Fig.12 The cross-sectional SEM image of the composite three-dimensional copper current collector of Example 7 is shown. It can be seen from the figure that when the deposition time is too long, the nanocones grow into irregular rod-like structures with a long length. This morphology is not conducive to the uniform deposition of lithium metal and also increases the mass of the current collector.
[0116] Example 8
[0117] This embodiment provides a composite three-dimensional copper current collector and a preparation method thereof. The preparation method is different from that in Example 1 in that the deposition time of the constant current electrodeposition is 2 minutes, and the other preparation methods and parameters are consistent with those in Example 1.
[0118] Fig.13 The surface SEM image of the composite three-dimensional copper current collector of Example 8 is shown. Fig.14 The cross-sectional SEM image of the composite three-dimensional copper current collector of Example 8 is shown. It can be seen from the figure that the surface of the current collector is a thin layer nanosheet structure and cannot form a nanocone structure to accommodate the initial nucleation of lithium metal.
[0119] Comparative Example 1
[0120] This comparative example provides a composite two-dimensional copper current collector and a preparation method thereof. The composite two-dimensional copper current collector is different from Example 1 in that the composite two-dimensional copper current collector comprises a planar two-dimensional copper current collector and dihexadecyl phosphate and n-hexyl mercaptan bound to the surface thereof;
[0121] The difference between the preparation method and Example 1 is that the process of preparing a three-dimensional copper current collector is omitted, and dihexadecyl phosphate and n-hexyl mercaptan are directly combined on the surface of a flat commercial copper foil after the oxide layer is removed and dried with high-purity nitrogen. The remaining preparation method and parameters are consistent with Example 1.
[0122] Comparative Example 2
[0123] This comparative example provides a three-dimensional copper current collector and a preparation method thereof. The difference between the composite three-dimensional copper current collector and Example 1 is that the surface of the three-dimensional copper current collector is not bound to self-assembly molecules, and the rest of the structure is consistent with Example 1;
[0124] The difference between the preparation method and Example 1 is that the step of combining dihexadecyl phosphate and n-hexyl mercaptan is omitted, and the remaining preparation method and parameters are consistent with Example 1.
[0125] Application Example 1-8, Comparative Application Example 1-2
[0126] The composite three-dimensional copper current collectors prepared in Examples 1 to 8 of the present invention, the composite two-dimensional copper current collectors prepared in Comparative Example 1, and the three-dimensional copper current collectors prepared in Comparative Example 2 were used as positive electrode sheets, respectively; the lithium sheet was used as the negative electrode sheet; the electrolyte was composed of 1M LiTFSI, DOL / DME (volume ratio 1:1), 2% LiNO 3 The ether-based electrolyte is used; the separator is a PP separator with a thickness of 25 μm; the above materials are assembled to obtain a half-cell, which corresponds to Application Examples 1-8 and Comparative Application Examples 1-2 respectively.
[0127] After the half-cells of Application Example 1-8 and Comparative Application Example 1-2 were left for 1 hour, the 2 The current density is 1 mAh / cm 2 The cycle stability test was carried out, and the specific test results are shown in Table 1.
[0128] Table 1
[0129] project The number of cycles when the half-cell charge and discharge efficiency begins to decay Application Example 1 315 Application Example 2 355 Application Example 3 293 Application Example 4 282 Application Example 5 227 Application Example 6 265 Application Example 7 255 Application Example 8 223 Comparative application example 1 165 Comparative Application Example 2 216
[0130] Application examples 9-16, comparative application examples 3-4
[0131] The composite three-dimensional copper current collectors prepared in Examples 1 to 8 of the present invention, the composite two-dimensional copper current collectors prepared in Comparative Example 1, and the three-dimensional copper current collectors prepared in Comparative Example 2 were used as positive electrode sheets, respectively, the lithium sheet was used as the negative electrode, and the electrolyte was composed of 1M LiTFSI, DOL / DME (volume ratio 1:1), 2% LiNO 3 Ether-based electrolyte, using 0.5mA / cm 2 2.5 mAh of lithium was pre-deposited on each surface at a current density of , and then the battery was disassembled in a glove box, and the current collector after lithium plating was taken out and rinsed with dimethyl ether (DME) solution and dried;
[0132] This method was used to prepare two identical lithium-plated current collectors, which were used to assemble a symmetrical battery, the positive electrode and the negative electrode, respectively. The electrolyte was composed of 1M LiTFSI, DOL / DME (volume ratio 1:1), and 2% LiNO 3 The ether-based electrolyte is used to assemble the above materials to obtain symmetrical batteries, which correspond to Application Examples 9-16 and Comparative Application Examples 3-4 respectively.
[0133] The symmetrical batteries of Application Examples 9-16 and Comparative Application Examples 3-4 were placed for 1 hour and then charged at 0.5 mA / cm 2 , 1mA / cm 2 , 2mA / cm 2 and 5mA / cm 2 The current density was cycled for 5 times and finally returned to 0.5 mA / cm 2 The current density was used to carry out the cycle stability test and the cycle time during short circuit was tested. The specific test results are shown in Table 2.
[0134] Fig.15 The symmetrical battery cycle performance comparison diagram of application example 11 and comparative application example 4 is shown. The results show that at different current densities, the overpotential of the battery modified by the self-assembled molecules is low, and even at 5 mA / cm 2 It can also operate stably under high current density and can be restored to stable circulation under low current density.
[0135] Table 2
[0136]
[0137]
[0138] Application examples 17-24, comparative application examples 5-6
[0139] The positive electrode plate uses 9 series ternary materials as active materials, wherein NMC:Super P:PVDF is mixed in a mass ratio of 90:5:5, wherein PVDF is prepared into a 4wt% solution with NMP as solvent, stirred for 6h by a homogenizer, and then evenly coated on the surface of commercial aluminum foil with a 150μm scraper, dried in a vacuum oven at 100℃ for 12h, and pressed into 12mm diameter discs (active material is 5mg) by a tablet press;
[0140] The composite three-dimensional copper current collectors prepared in Examples 1 to 8 of the present invention, the composite two-dimensional copper current collectors prepared in Comparative Example 1, and the three-dimensional copper current collectors prepared in Comparative Example 2 were used as positive electrode sheets, respectively, the lithium sheet was used as the negative electrode, and the electrolyte was composed of 1M LiTFSI, DOL / DME (volume ratio 1:1), 2% LiNO 3 Ether-based electrolyte, using 0.5mA / cm 2 2.5 mAh of lithium was pre-deposited on each surface at a current density of 1.5 mAh. The battery was then disassembled in a glove box, the current collector after lithium plating was taken out, rinsed with dimethyl ether (DME) solution, and dried to obtain the negative electrode sheet. The electrolyte was composed of 1 M LiPF 6, EC:EMC:DEC volume ratio of 1:1:1, 1% LiDFOB lipid electrolyte; the diaphragm is a 25μm PP diaphragm, and the above materials are assembled to obtain a lithium metal full battery, corresponding to Application Examples 17-24 and Comparative Application Examples 5-6 respectively.
[0141] After the lithium metal full batteries of Application Examples 17-24 and Comparative Application Examples 5-6 were left for 12 hours, a cycle stability test was performed at 0.3C. The discharge capacity after 100 cycles at 0.3C was tested. The specific test results are shown in Table 3.
[0142] Table 3
[0143] project <![CDATA[Full cell discharge capacity at 0.3C for 100 cycles (mAh g -1 )]]> Application Example 17 183.2 Application Example 18 186.5 Application Example 19 181.7 Application Example 20 180.6 Application Example 21 169.8 Application Example 22 173.6 Application Example 23 172.3 Application Example 24 168.2 Comparative Application Example 5 155.9 Comparative Application Example 6 165.6
[0144] The test results show that:
[0145] (1) It can be seen from the half-cell performance of Application Examples 1-4 corresponding to Examples 1-4, the symmetric battery performance of Application Examples 9-12, and the full battery performance of Application Examples 17-20 that the structure of the composite three-dimensional copper current collector of the present invention, that is, the composite three-dimensional copper current collector includes a three-dimensional copper current collector and self-assembled molecules, wherein the three-dimensional copper current collector includes a copper foil and a copper-nickel alloy nanocone loaded on one side of the copper foil, and the surface of the copper-nickel alloy nanocone is combined with the self-assembled molecules. By combining the self-assembled molecules with different functions, the three-dimensional copper current collector can be further modified in different aspects, and can be applied to various types of batteries to significantly improve the electrochemical performance; wherein, when the half-cell charge and discharge efficiency decays, the number of cycles can reach more than 270 cycles, and can reach up to 355 cycles, when the symmetric battery is short-circuited, the cycle time can reach more than 950 hours, and can reach up to 1055 hours, and the full battery 0.3C 100 cycle discharge capacity can reach 180mAh g -1 Above, up to 186.5mAh g -1 ;
[0146] Furthermore, when the self-assembling molecules include long-chain self-assembling molecules and short-chain self-assembling molecules (Examples 1 and 2), the two act synergistically. Since the long-chain self-assembling molecules have a large steric hindrance, after they self-assemble with the three-dimensional copper current collector, there are still sites on the surface of the three-dimensional copper current collector that are not completely coated. Further, the short-chain self-assembling molecules with smaller steric hindrance continue to assemble and coat the uncoated sites. The two work together and work synergistically to make the coating denser, and the obtained composite three-dimensional copper current collector has better performance.
[0147] (2) It can be seen from the half-cell performance of application examples 5-8 corresponding to embodiments 5-8, the symmetrical cell performance of application examples 13-16, and the full cell performance of application examples 21-24 that the present invention further regulates the current density of constant current electrodeposition to 2-2.5 mA / cm 2The deposition time of constant current electrodeposition is 10-100min. A nanocone array structure with uniform morphology can be loaded on one side of the copper foil. After assembling various types of batteries, the electrochemical performance is excellent.
[0148] (3) It can be seen from the half-cell performance of comparative application example 1, the symmetrical cell performance of comparative application example 3, and the full-cell performance of comparative application example 5 corresponding to comparative example 1 that when the self-assembling molecules are directly combined on the surface of the two-dimensional copper current collector, the problem of dendrite growth cannot be effectively suppressed, which will significantly reduce the electrochemical performance of various types of batteries after assembly.
[0149] (4) It can be seen from the half-cell performance of Comparative Application Example 2 corresponding to Example 2, the symmetric cell performance of Comparative Application Example 4, and the full-cell performance of Comparative Application Example 6 that when the surface of the three-dimensional copper current collector is not bound to the self-assembled molecules, the surface of the three-dimensional copper current collector is easily corroded, and the solvent brought by the super-wetting characteristics makes the contact surface area too large, and the organic solvent decomposes to form an unfavorable organic component SEI, which will significantly reduce the electrochemical performance of various types of batteries after assembly.
[0150] In summary, the present invention combines self-assembling molecules on the surface of a three-dimensional copper current collector to modify it, and combines a three-dimensional copper current collector that is thin, light, and has excellent mechanical properties, but has poor corrosion resistance, weak antioxidant ability, and many side reactions with self-assembling molecules with different functions. This can improve the three-dimensional copper current collector's easy oxidation and poor corrosion resistance, surface side reactions, and lithium dendrite growth. The three-dimensional copper current collector can be modified in different aspects, and the composite three-dimensional copper current collector can be used in a lithium metal battery, which can significantly improve the electrochemical properties of the lithium metal battery, such as the rate and cycle stability.
[0151] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite three-dimensional copper current collector, characterized in that: The composite three-dimensional copper current collector comprises a three-dimensional copper current collector and self-assembly molecules; The three-dimensional copper current collector includes a copper foil and a copper-nickel alloy nanocone supported on one side surface of the copper foil; The self-assembly molecules are combined on the surface of the copper-nickel alloy nanocones.
2. The composite three-dimensional copper current collector according to claim 1, characterized in that: The copper-nickel alloy nanocones are arranged in an array; Preferably, the height of the copper-nickel alloy nanocones is 3.5-20 μm; Preferably, the bottom diameter of the copper-nickel alloy nanocone is 800-1500 nm; Preferably, the density of the copper-nickel alloy nanocones is 1×10 6 ~1×10 7 Pieces / mm 2 .
3. The composite three-dimensional copper current collector according to claim 1 or 2, characterized in that: The self-assembling molecules include long-chain self-assembling molecules and / or short-chain self-assembling molecules; Preferably, the long-chain self-assembling molecules and the short-chain self-assembling molecules each independently include a group of an element containing a lone pair of electrons; Preferably, the element containing a lone pair of electrons includes any one of S, O or N or a combination of at least two thereof; Preferably, the long-chain self-assembling molecule comprises any one or a combination of at least two of dihexadecyl phosphate, n-octadecyl phosphate, perfluorotetradecyl phosphate, n-tetradecyl mercaptan, n-hexadecyl mercaptan or n-octadecyl mercaptan; Preferably, the short-chain self-assembly molecule comprises any one of thiocyanuric acid, melamine, cyanuric acid, benzotriazole, 2-mercaptobenzothiazole, thiourea, urea, n-butyl mercaptan, n-pentyl mercaptan, n-hexyl mercaptan, n-heptyl mercaptan or n-octyl mercaptan, or a combination of at least two thereof.
4. A method for preparing a composite three-dimensional copper current collector according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: A constant current electrodeposition process is adopted to load copper-nickel alloy nanocones on the surface of copper foil to obtain a three-dimensional copper current collector; and self-assembly molecules are then combined on the surface of the three-dimensional copper current collector to obtain a composite three-dimensional copper current collector.
5. The preparation method according to claim 4, characterized in that: The current density of the constant current electrodeposition is 2-2.5 mA / cm 2 ; Preferably, the deposition time of the constant current electrodeposition is 10-100 min; Preferably, the working electrode of the constant current electrodeposition is the copper foil, and the counter electrode is a copper sheet having the same area as the copper foil in the working electrode.
6. The preparation method according to claim 4 or 5, characterized in that: The electrolyte of the electrodeposition process includes copper sulfate, sodium hypophosphite, nickel sulfate, trisodium citrate, boric acid, polyethylene glycol and sodium hydroxide; Preferably, in the electrolyte, the concentration of copper sulfate is 0.02-0.04 mol / L, the concentration of sodium hypophosphite is 0.1-0.4 mol / L, the concentration of nickel sulfate is 0.0015-0.005 mol / L, the concentration of trisodium citrate is 0.03-0.07 mol / L, the concentration of boric acid is 0.3-1 mol / L, and the concentration of polyethylene glycol is 1-15 g / L; Preferably, the temperature of the electrolyte is 60-80°C; Preferably, the pH of the electrolyte is 7-9.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The method used for combining the self-assembling molecules includes a liquid phase method or a vapor phase deposition method, preferably a liquid phase method; Preferably, the liquid phase method comprises the following steps: The three-dimensional copper current collector is immersed in a solution containing self-assembly molecules and placed in a constant temperature water bath, so that the self-assembly molecules are combined with the surface of the three-dimensional copper current collector.
8. The preparation method according to claim 7, characterized in that: The solvent containing the self-assembling molecular solution includes any one of anhydrous ethanol, tetrahydrofuran, anhydrous cyclohexane, toluene or dimethyl sulfoxide, or a combination of at least two thereof; Preferably, the temperature of the constant temperature water bath is 50-120°C; Preferably, the constant temperature water bath is kept for 1-120 min.
9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: The copper foil is used as a working electrode after removing the oxide layer and being blown dry with high-purity nitrogen. A copper sheet with the same area as the copper foil in the working electrode is used as a counter electrode. The distance between the working electrode and the counter electrode is 1-5 cm. The electrolyte includes 0.02-0.04 mol / L copper sulfate, 0.1-0.4 mol / L sodium hypophosphite, 0.0015-0.005 mol / L nickel sulfate, 0.03-0.07 mol / L trisodium citrate, 0.3-1 mol / L boric acid, 1-15 g / L polyethylene glycol and sodium hydroxide. The pH of the electrolyte is 7-9, the temperature is 60-80° C., and constant current electrodeposition is used at 2-2.5 mA / cm 2 The copper foil electrode is deposited for 10-100 minutes to obtain a three-dimensional copper current collector; After removing the oxide layer of the three-dimensional copper current collector and drying it with high-purity nitrogen, the three-dimensional copper current collector is immersed in a solution containing self-assembled molecules, and immersed in a constant temperature water bath of 50-120° C. for 1-120 minutes to allow the self-assembled molecules to combine with the surface of the three-dimensional copper current collector. After the immersion is completed, the surface is rinsed, and the surface is dried with high-purity nitrogen and vacuum dried to obtain a composite three-dimensional copper current collector.
10. A lithium metal battery, characterized in that: The lithium metal battery comprises the composite three-dimensional copper current collector according to any one of claims 1 to 3, or the composite three-dimensional copper current collector prepared by the preparation method according to any one of claims 4 to 9; Preferably, the lithium metal battery comprises a liquid lithium metal battery or a solid lithium metal battery.
Citation Information
Cited By
Laser-etched three-dimensional alloy zinc negative electrode material and preparation method and application thereof
CN120998947A